Decentering the researcher in intimate scholarship : critical posthuman methodological perspectives in education - Strom, Kathryn J.; Mills, Tammy; Ovens, Alan (Advances in research on teaching, 2018)
"Intimatescholarship" refers to qualitative methodologies, such as self-study and autoethnography, that directly engage the personal experience, knowledge, and/or practices of the researcher(s) as the focus ofinquiry. While intimate scholarship offers entry points into non-binary thinking by blurring the line between researcher/researched, much work in this genre continues to reinforce a humanist "I". In this volume, we ask what happens when the researcher in forms of intimate scholarship is decentered, or is considered as merely one part of an entangled material-discursive formation. Chapters in this volume highlight ways that researchers of teaching and teacher education can advance conversations in education while exploring theories with an ontological view of the world as fundamentally multiple, dynamic, and fluid. Drawing on a range of methods, authors "put to work" posthuman, non-linear, and multiplistic theories and concepts to disrupt and decenter the "I" in intimate methodologies. Also featured in this volume are conversations with leading posthuman scholars, who highlight the possibilities and challenges of decentering the researcher inintimate scholarship as a practice of social justice research.